Silene oxelmanii (Caryophyllaceae), a new species from Iran - Gholipour, Abbas (Phytotaxa, 2017)
Silene oxelmanii sp. nov. (sect. Auriculatae, Caryophyllaceae) is described as a new species from CW-Iran. The new species is a rhizomatous perennial herb morphologically similar to S. eriocalycina from which differs in having shorter leaves and alar pedicel, a longer and tomentose calyx and antophore and a capsule included in calyx. A distribution map, ecological remarks, original illustration and photos of the new species are presented.